Growth models and nutriente uptake curve of tomato BRS 1509 subjected to irrigation pulses - Moreira de Carvalho, Diego Bexiga; de Souza, Angela Vacarro [UNESP]; Domingues Neto, Francisco José [UNESP]; Iglesias, Luara [UNESP]; Nogueira, Bianca Bueno [UNESP]; Zanetti, Willian Aparecido [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP]; Putti, Fernando Ferrari [UNESP] (Taylor & Francis, 2020)
Tomato is a high-scale production vegetable, being today the second most produced in the world. Brazil is the largest producer of tomatoes in South America, and its cultivation is one of the most important in the category of hybrids. BRS 1509 is one of these crops that needs to be observed for behavior in the developmental phases of the plant. With this, the objective of this study is to determine the curve of nutrient uptake in tomato cv. BRS 1509. A randomized block design was used with 10 treatments, consisting of the sampling times 20, 30, 40, 50, 60, 70, 80, 90, 100 and 110 days after the transplant of the seedlings. The applied nutrients for the fertirrigations. The collected samples were fractionated in leaves, stems, fruits and roots. At this moment, the biometric parameters of the crop were determined, in which the number of leaves, fresh mass of leaves and stems, diameter and stem length, and the dry mass of these components were determined. The most absorbed nutrients were N, Ca and P, predominating their concentration in the dry mass of the fruits. The determination of the absorption curve of tomato BRS 1509 grown on coconut fiber substrates demonstrates through the sampling times the necessary amount of nutrients that must be submitted to the fertilization process and where the greatest accumulation and better productive utilization occurs.
Keywords: fertigation; nutrient absorption; pulse irrigation; tomato culture